Nepenthes parvula (Nepenthaceae), a new species from Cape York, Queensland, Australia - Wilson, Gary W.; Venter, Stephanus (Phytotaxa, 2016)
A new species, Nepenthes parvula (Nepenthaceae), is described from Cape York Peninsula, Queensland, Australia. The species is regarded as new based on the overall small stature, small mature pitchers and the old leaves with pitchers that are retained, distinct fine-scale morphological characteristics, and discrete habitat occupied.